Unusual Case of Long Drop Hanging with Sub-occipitomastoid Ligature Knot and Cut Throat Injury over the Laryngotracheal Region: Forensic and Medico-legal Implications - Raghav, Narendra K. Singh; Singh, Vivek K; Khokhar, Gursirat; Shankar Pai, Aaryan; Singh, Nrashant (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Suicide ranks as the primary cause of mortality among Indian individuals between 15 and 34 years old. The investigation of crime scenes is essential to distinguish between suicide and homicide cases. People who suffer cut-throat injuries are more likely to have been murdered than to have killed themselves. Suicidal incised wounds most commonly appear in the anterior neck area next to the laryngo-tracheal region and often show signs of hesitational cuts. Case Presentation: The victim, a 25-year-old male, average build, used a razor blade to create an incised wound in his laryngo-tracheal region before ending his life through hanging. The deceased committed suicide in his parents’ house by using a bedsheet as a soft ligature that was attached to a ceiling fan with the help of a chair. Fatal asphyxia resulted from neck constriction and soft tissue trauma due to the specific length and placement of the ligature. The knot of the ligature was located at the sub-occipitomastoid area on his neck. The investigation of this unique case focuses on understanding how neck trauma played a role in causing death. Conclusion: This research presents an atypical suicide case involving self-inflicted damage to the laryngo-tracheal area combined with a ligature knot positioned at the sub-occipitomastoid region. Forensic experts conducted an extensive examination that involved analyzing the crime scene structure, body placement, and blood splatter patterns to establish the manner of death. No defensive injuries combined with hesitation marks and knot placement, along with bloodstains on fingertips and seminal discharge, indicated suicide as the cause of death. The case demonstrates how autopsy results combined with detailed scene examination are essential to differentiate between suicide and homicide in difficult cases.